A Rare Case of Cryptococcal Meningitis in a Child with a Congenital Heart Disease - Bhim Gopal Dhoubhadel; Ujjwal Laghu; Raju Poudel; Konosuke Morimoto; Koya Ariyoshi (Case Reports in Infectious Diseases)
Cryptococcal meningitis, which has a high mortality rate, is rare in immunocompetent children. Although many immunocompromised conditions are identified as predisposing factors, congenital heart disease in children is not well recognized as a predisposing factor for the disease. A 12-year-old female child presented with a progressively increasing headache for one month. There was history of vomiting and fever off and on. On examination, she had a pansystolic murmur and meningeal signs. Lumbar puncture was done; opening pressure was high (27 cm H2O) and white blood cell (WBC) count in cerebrospinal fluid (CSF) was slightly high. Gram staining, India ink preparation, and culture of CSF were negative. Cryptococcal antigen (CrAg) test was not available. Echocardiography showed a 12 mm ventricular septal defect (VSD). The patient was diagnosed as meningitis with VSD and treated with intravenous ceftriaxone and vancomycin; however, she did not improve after 7 days of antimicrobial treatment. She was then transferred to another hospital where India ink and culture of CSF showed cryptococcus; CrAg test was done, and it was positive. Despite the treatment with lyposomal amphotericin B and flucytosine, she died on 9th day of admission in pediatric intensive care unit. It is necessary for global advocacy for need of availability of CrAg test in resource-limited regions. Treating doctors should consider VSD, a congenital heart disease, as a predisposing factor for cryptococcal meningitis in children. As CrAg is more sensitive than India ink and culture, it should be the first line of investigation in suspected cases.